The co-chaperone SGT of Leishmania donovani is essential for the parasite's viability - Ommen, Gabi (Springer Netherlands, 2009)
Molecular chaperone proteins play a pivotal role in the protozoan parasite Leishmania donovani, controlling cell fate and ensuring intracellular survival. In higher eukaryotes, the so-called co-chaperone proteins are required for client protein recognition and proper function of chaperones, among them the small glutamine-rich tetratricopeptide repeat proteins (SGT) which interact with both HSP70 and HSP90 chaperones. An atypical SGT homolog is found in the L. donovani genome, encoding a protein lacking the C-terminal glutamine-rich region, normally typical for SGT family members. The gene is expressed constitutively during the life cycle and is essential for survival and/or growth of the parasites. LdSGT forms large, stable complexes that also include another putative co-chaperone, HSC70 interacting protein (HIP). The gene product forms cytoplasmic clusters, matching the subcellular distribution of HIP and partly that of the major cytoplasmic chaperones, HSP70 and HSP90, reflecting a direct molecular interaction with both chaperones. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12192-009-0160-7) contains supplementary material, which is available to authorized users.